2016
DOI: 10.1038/mp.2016.47
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythm dysfunction: a novel environmental risk factor for Parkinson’s disease

Abstract: Parkinson's disease (PD) is a chronic and progressive neurodegenerative disorder. Although rare genetically linked cases of PD have been reported, most incidences are sporadic in nature. Late-onset, sporadic PD is thought to result from the combined effects of genetic and environmental risk factors exposure. Sleep and circadian rhythm disorders are recurrent among PD patients and appear early in the disease. Although some evidence supports a relationship between circadian disruption (CD) and PD, whether this i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 22 publications
1
60
0
Order By: Relevance
“…Importantly, rhythms in clock gene expression in the dorsal striatum are sensitive to changes in dopamine release (Verwey et al 2016). Circadian disruption by triggering a robust neuroinflammatory reaction and degeneration of the nigral-dopaminergic neuronal system exacerbates process of PD (Lauretti et al 2016). Consisted with PD patients and PD models, our presented study also found disrupted expressions of circadian clock feedback genes Per1 and Per2 in PD rat model, similar to our recent publication in Mn-induced PD-like neurodegeneration (Li et al 2017b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, rhythms in clock gene expression in the dorsal striatum are sensitive to changes in dopamine release (Verwey et al 2016). Circadian disruption by triggering a robust neuroinflammatory reaction and degeneration of the nigral-dopaminergic neuronal system exacerbates process of PD (Lauretti et al 2016). Consisted with PD patients and PD models, our presented study also found disrupted expressions of circadian clock feedback genes Per1 and Per2 in PD rat model, similar to our recent publication in Mn-induced PD-like neurodegeneration (Li et al 2017b).…”
Section: Discussionmentioning
confidence: 99%
“…Circadian dysfunction has been observed in PD patients and in animal PD models including mice, rats, dogs, and non-human primates (Videnovic and Willis 2016), which may result in negative consequences to the homeostasis and even exacerbate the disease progression (Chahine et al 2016; Li S et al 2017; Willison et al 2013). Circadian rhythm dysfunction is now considered as a novel environmental risk factor for PD (Lauretti et al 2016), and a novel diagnostic and therapeutic target in PD and neurodegenerative disorders (Videnovic and Willis 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There are perturbations of the circadian system in neurodegenerative diseases, including PD (sometimes before any motor symptoms), and their animal models, as reviewed [29]. The inverse relationship–circadian disruption causing neuronal loss–remains hypothetical, but is consistent with a recent study in mice [30]. …”
Section: Introductionmentioning
confidence: 63%
“…Although there was no evidence of a melatonin phase shift in patients with Parkinson's disease compared to controls, alterations in melatonin secretion were significantly correlated with objective sleep parameters including sleep latency and reduced slow-wave sleep [7]. Interestingly, Lauretti et al showed that circadian rhythm disruption may contribute to 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced neurotoxicity, suggesting that circadian disturbances might be a driving force for neurodegenerative processes [25]. However, symptomatic treatment with exogenous melatonin in patients with idiopathic RBD did not affect neurodegenerative outcome [26 && ].…”
Section: Disruption Of Circadian Rhythmmentioning
confidence: 99%